Development of an Energy-Efficient Electrical Load Model for Optimizing Electricity Consumption in the Headquarters Building using the PDCA Approach - Budiman, Refki; Faizal, Jhonny (LPPM Universitas Andalas, 2025)
The increasing electricity consumption in the public building sector has a significant impact on greenhouse gas (CO2) emissions, which is proportional to the volume of energy used. This study aims to develop an energy-efficient electrical load model to optimize electricity consumption in the headquarters building of PT Semen Padang using the Plan-Do-Check-Action (PDCA) approach. In the Plan stage, problem identification was conducted through a Pareto diagram and root cause analysis using a fishbone diagram. The dominant issue identified was energy waste in the lighting system. The solution implemented included the installation of motion sensor-based switch control devices to regulate lighting use automatically. In the Do phase, the devices were installed and tested, while in the Check phase, the evaluation showed a reduction in electricity consumption from over 85,000 kWh per month to below 80,000 kWh per month, resulting in an electricity cost savings of IDR 31 million per month. The Action phase established standards for inputs, processes, and outputs to ensure the sustainability of the improvements made. This study not only provides financial benefits but also supports the company's Energy Management System policy. With the PDCA approach, improvement processes can be carried out systematically and continuously, making a tangible contribution to energy efficiency in the public building sector.